Genetic variants of genes in the NER pathway associated with risk of breast cancer: A large‐scale analysis of 14 published GWAS datasets in the DRIVE study - Ge, Jie; Liu, Hongliang; Qian, Danwen; Wang, Xiaomeng; Moorman, Patricia G.; Luo, Sheng; Hwang, Shelley; Wei, Qingyi (International journal of cancer, 2019)
A recent hypothesis‐free pathway‐level analysis of genome‐wide association study (GWAS) datasets suggested that the overall genetic variation measured by single nucleotide polymorphisms (SNPs) in the nucleotide excision repair (NER) pathway genes was associated with breast cancer (BC) risk, but no detailed SNP information was provided. To substantiate this finding, we performed a larger meta‐analysis of 14 previously published GWAS datasets in the Discovery, Biology and Risk of Inherited Variants in Breast Cancer (DRIVE) study with 53,107 subjects of European descent. Using a hypothesis‐driven approach, we selected 138 candidate genes from the NER pathway using the “Molecular Signatures Database (MsigDB)” and “PathCards”. All SNPs were imputed using IMPUTE2 with the 1000 Genomes Project Phase 3. Logistic regression was used to estimate BC risk, and pooled ORs for each SNP were obtained from the meta‐analysis using the false discovery rate for multiple test correction. RegulomeDB, HaploReg, SNPinfo and expression quantitative trait loci (eQTL) analysis were used to assess the SNP functionality. We identified four independent SNPs associated with BC risk, BIVM‐ERCC5 rs1323697_C (OR = 1.06, 95% CI = 1.03–1.10), GTF2H4 rs1264308_T (OR = 0.93, 95% CI = 0.89–0.97), COPS2 rs141308737_C deletion (OR = 1.06, 95% CI = 1.03–1.09) and ELL rs1469412_C (OR = 0.93, 95% CI = 0.90–0.96). Their combined genetic score was also associated with BC risk (OR = 1.12, 95% CI = 1.08–1.16, ptrend < 0.0001). The eQTL analysis revealed that BIVM‐ERCC5 rs1323697 C and ELL rs1469412 C alleles were correlated with increased mRNA expression levels of their genes in 373 lymphoblastoid cell lines (p = 0.022 and 2.67 × 10−22, respectively). These SNPs might have roles in the BC etiology, likely through modulating their corresponding gene expression. What's new? Although breast carcinogenesis is still not fully understood, a variety of risk factors have been identified, some of them with mechanisms likely involved in DNA damage and repair. This study identified four novel independent SNPs in the nucleotide excision repair (NER) pathway genes (BIVM‐ERCC5 rs1323697_C, GTF2H4 rs1264308_T, COPS2 rs141308737_C deletion and ELL rs1469412_C) to be associated with breast cancer risk. BIVM‐ERCC5 rs1323697_C and ELL rs1469412_C alleles were correlated with increased mRNA expression. These findings suggest that variants in the NER pathway genes play an important role in the development of breast cancer, possibly by influencing gene expression.